Odpowiedzi

2010-01-14T20:28:01+01:00
Moze podasz str. z pod. jesli tio z pod. ?!
  • Sunn
  • Rozwiązujący
2010-01-14T20:29:30+01:00
A)

5x+3y=0
-x-2y=7/*5

5x+3y=0
-5x-10y=35

7y=35
y=5
x=-3

b)
3s+5t=-6
1,5s-2t=-3/*(-2)

3s+5t=-6
-3s+4t=6

9t=0
t=0
s=-2



c)

-x+y=5
x+y=5

2y=10
y=5
x=0

d)

x-2y=4
-x+3y=0

y=4
x=12
2010-01-14T20:35:49+01:00
A)
5x+3y=0
-x-2y=7 /*5

5x+3y=0
-5x-10y=35

-7y=35/:(-7)
y=(-5)

y=(-5)
5x+3y=0

y=(-5)
5x=-3y

y=(-5)
5x=(-3)*(-5)

y=(-5)
5x=15/:5

y=(-5)
x=3

b)
3s+5t=-6
1,5s-2t=-3/*(-2)

3s+5t=-6
-3s+4t=6

9t=0/:9
t=0

t=0
3s+5t=-6

t=0
3s=-6-5t

t=0
3s=-6/:3

t=0
s=-2

c)
-x+y=5
x+y=5

2y=10/:2
y=5

y=5
x+y=5

y=5
x=5-y

y=5
x=5-5

y=5
x=0

d)
x-2y=4
-x+3y=0

y=4

y=4
x-2y=4

y=4
x=4+2y

y=4
x=4+8

y=4
x=12

Mam nadzieję, że pomogłam. :)